Value of IgA tTG in Predicting Mucosal Recovery in Children with Celiac Disease on a Gluten Free Diet - Leonard, Maureen M. (J Pediatr Gastroenterol Nutr, 2017)
OBJECTIVE: Our objective was to determine the rate of mucosal recovery in pediatric patients with celiac disease on a gluten free diet. We also sought to determine whether IgA tissue transglutaminase (tTG) correlates with mucosal damage at the time of a repeat endoscopy with duodenal biopsy in these patients. METHODS: We performed a retrospective chart review of one-hundred and three pediatric patients, under 21 years of age, with a diagnosis of celiac disease defined as Marsh 3 histology, and who underwent a repeat endoscopy with duodenal biopsy at least twelve months after initiating a gluten free diet. RESULTS: We found that 19% of pediatric patients treated with a gluten free diet had persistent enteropathy. At the time of the repeat biopsy, tTG was elevated in 43% of cases with persistent enteropathy and 32% of cases in which there was mucosal recovery. Overall the positive predictive value of the autoantibody tissue transglutaminase was 25% and the negative predictive value was 83% in patients on a gluten free diet for a median of 2.4 years. CONCLUSIONS: Nearly one in five children with celiac disease in our population had persistent enteropathy despite maintaining a gluten free diet and IgA tTG was not an accurate marker of mucosal recovery. Neither the presence of symptoms nor positive serology were predictive of a patient’s histology at the time of repeat biopsy. These findings suggest a revisitation of monitoring and management criteria of celiac disease in childhood.